A educação para o diálogo inter-religioso na escola pública brasileira: uma aliada à cultura da paz - Marinho, Nilton Pereira (2014)
This thesis analyzes the existence of a strong religious influence in Brazilian education, researching Brazil as a secular country although with religious reminiscences, pointing to possible historical causes for the secularism of the Brazilian state in its intrinsic relation with Religious Education (ER) in the directing board of Education for Inter-Religious Dialog (EPDIR) based on the principle of Inter- Religious Dialog (DIR). The first chapter, fruit of a monograph which was elaborated by the author of the research and inspired in the discipline of Latin American Hermeneutics taught by professor Wilhelm Wachholz, analyzes the establishment of secularism in the Brazilian State, highlighting three founding conflicts in the national history: The conflict between Marquês de Pombal and the Companhia de Jesus [Jesuits] in Colonial Brazil, the religious issue in Imperial Brazil and the Canudos War in Republican Brazil. These three conflicts were analyzed as reliefs of the wear in the relation between the church and the state in Brazil. The second chapter, also fruit of another monograph written by the author of the thesis and inspired in the disciplines of Religion and Education in Latin America by professor Rudolf von Sinner, Personality and Faith by professor Gisela Streck and Foundations and Tendencies of Education by professor Remí Klein with his pedagogical letters, analyzes how various religious traditions can, through their common ground ethical values, give a great contribution to a culture of peace, and at the same time it analyzes the possibility of religious fundamentalism becoming one of the main divisive elements of humanity. In the third chapter the author analyzes the historical relation of the seven constitutions in Brazil and ER. It envisions the implications of the principle of DIR for the formation of ER professors in a licentiate program and a curricular proposal of ER based on Education for Inter-Religious Dialog in national education through the schools which would result in a culture of inter-religious dialog and of respect for the religion of the other, contributing to the promotion of a more tolerant, just and harmonious society, diminishing the idea that the devil is the other and increasing the idea of otherness in which in disgrace, in hunger and in injustice all are the same.